Left atrial speckle tracking echocardiography in clinically healthy dogs: Variability and prediction intervals. (January 2021) - Baron Toaldo, M.; Bini, M.; Romito, G.; Guglielmini, C.; Cipone, M.; Contiero, B.
Highlights: Speckle tracking echocardiography allowed measurement of left atrial (LA) deformation. Strain and strain rate were influenced by bodyweight (BW). With increasing BW, LA strain decreased and diastolic strain rate increased. BW-dependent LA strain and strain rate prediction intervals were proposed. Abstract: Left atrial (LA) speckle tracking echocardiography (STE) provides indices of LA deformation such as strain and strain rate. These variables offer useful clinical information in human and canine patients with cardiac disease. At present, reference ranges for LA STE variables in dogs are scarcely established and, due to variability among centers, they cannot be accepted worldwide. The present study aimed to provide normal ranges for LA strain and strain rate variables in clinically healthy dogs, and to evaluate the effect of clinical parameters such as bodyweight. Eighty clinically healthy dogs served as the study population. Left atrial STE was feasible in all dogs and agreement within and between observers was clinically acceptable for most of the variables, in particular strain variables. Age, sex, and heart rate did not affect LA STE. Bodyweight was negatively correlated with strain variables and positively correlated with diastolic strain rate variables and the relationship was allometric. Bodyweight-based vendor-dependent prediction intervals for LA STE variables in clinically healthy dogs could aid the evaluation of LA function in clinical practice.